Viral R plasmid Rphi6P: properties of the penicillinase plasmid prophage and the supercoiled, circular encapsidated genome. - Tucker, W T (1978)
Properties of the viral R plasmid Rphi6P are described. As a temperate bacteriophage, it plaques on the facultative phototroph Rhodopseudomonas sphaeroides. Under aerobic conditions the phage had a latent period of 180 min, a burst time of 200 min, and a burst size of 15 to 20 particles per infective center. The encapsidated viral genome occurred as a supercoiled, circular DNA duplex with a mean contour length of 16.5 +/- 10 micron. Percent guanine plus cytosine, as calculated from thermal denaturation profiles, was 63.5. Mitomycin C-induced loss of the prophage suggested an extrachromosomal location in the host cell. Use of this curing agent enabled the isolation of a plasmid-free strain of R. sphaeroides. Biophysical analysis of the plasmid-free strain lysogenized with Rphi6P confirmed that the prophage occurred as a plasmid in the host cell.